A study on impact of employee training on project performance in construction industry in Kota Bharu, Kelantan - Nik Alia Haifaa, Nik Adik (2014)
The purpose of this study is to determine the relationship between employee training (on the job training and off the job training), and the project performance in construction industry in Kota Bharu, Kelantan. In this research, the function is getting a response and difference idea to questions on what is the impact of employee training to the project performance in the related construction industry. The term in this research is ‘‘employee training” and ‘‘project performance’’ which find the way of this factor that contribute the construction industry in achieving their target. The main target is the result of good project performance after the completion of the project. A total of 48 sample size of participants which is contractors Grade 4 have completed the research study. Quantitative method and questionnaires have been used as the main instruments to collect the data. The questionnaires are consisted of three sections that are:- Section A: Demographic, Section B: Employee Training, section C: Project Performance. The data that are collected has been analyzed using Statistical Package for the Social Science (SPSS) database software. Reliability analysis, Pearson correlation analysis, regression analysis and analysis of hypothesis had been use to analyze the data. Based on the regression analysis that had been done, it shows that the hypothesis is accepted. As a conclusion, there is a positive relationship between employee training and project performance